Dopamine D1/D5 receptor signaling is involved in arrhythmogenesis in the setting of takotsubo cardiomyopathy - Huang, Mengying; Yang, Zhen; Li, Yingrui; Lan, Huan; Cyganek, Lukas; Yücel, Gökhan; Lang, Siegfried; Bieback, Karen; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Frontiers in Cardiovascular Medicine, 2022)
BackgroundPrevious studies suggested involvement of non-ß-adrenoceptors in the pathogenesis of Takotsubo cardiomyopathy (TTC). This study was designed to explore possible roles and underlying mechanisms of dopamine D1/D5 receptor coupled signaling in arrhythmogenesis of TTC.MethodsHuman-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were challenged by toxic concentration of epinephrine (Epi, 0.5 mM for 1 h) for mimicking the catecholamine excess in setting of TTC. Specific receptor blockers and activators were used to unveil roles of D1/D5 receptors. Patch clamp, qPCR, and FACS analyses were performed in the study.ResultsHigh concentration Epi and two dopamine D1/D5 receptor agonists [(±)-SKF 38393 and fenoldopam] reduced the depolarization velocity and prolonged the duration of action potentials (APs) and caused arrhythmic events in iPSC-CMs, suggesting involvement of dopamine D1/D5 receptor signaling in arrhythmogenesis associated with QT interval prolongation in the setting of TTC. (±)-SKF 38393 and fenoldopam enhanced the reactive oxygen species (ROS)-production. H2O2 (100 μM) recapitulated the effects of (±)-SKF 38393 and fenoldopam on APs and a ROS-blocker N-acetylcysteine (NAC, 1 mM) abolished the effects, suggesting that the ROS-signaling is involved in the dopamine D1/D5 receptor actions. A NADPH oxidases blocker and a PKA- or PKC-blocker suppressed the effects of the dopamine receptor agonist, implying that PKA, NADPH oxidases and PKC participated in dopamine D1/D5 receptor signaling. The abnormal APs resulted from dopamine D1/D5 receptor activation-induced dysfunctions of ion channels including the Na+ and L-type Ca2+ and IKr channels.ConclusionsDopamine D1/D5 receptor signaling plays important roles for arrhythmogenesis of TTC. Dopamine D1/D5 receptor signaling in cardiomyocytes might be a potential target for treating arrhythmias in patients with TTC.